The genetic characterization of myrmelachista roger assemblages (hymenoptera: formicidae: formicinae) in the atlantic forest of southeastern Brazil - Nakano, Márcia Akemi; Miranda, Vitor Fernandes [UNESP]; Feistosa, Rodrigo Machado; Morini, M. S.C. (Univ Estadual Feira Santana, 2014)
Arboreal ants of the genus Myrmelachista, which have ecologically important relationships with different vegetable species, are found exclusively in the Neotropical region. These ant species are difficult to identify, and their taxonomy remains controversial; moreover, little is known regarding their biology. The objective of the present work is to assess the genetic similarities and dissimilarities between and within Myrmelachista species, with the goal of expanding knowledge of the relationships among the taxa of this genus. Sample collection in selected regions of the dense ombrophile forest of southeastern Brazil yielded 256 nests, which were found in vegetation or among scattered twigs in the leaf litter; eight species were recorded. A total of 180 specimens were analyzed, producing 123 polymorphic fragments. Data analyses revealed similarity relationships that allowed the examined species to be classified into the following groups: (1) Myrmelachista sp. 4, M. nodigera, M. ruszkii and M. gallicola; (2) M. catharinae and M. arthuri; (3) M. reticulata; and (4) Myrmelachista sp. 7. The study results also revealed the existence of two morphological variants of M. catharinae; M. arthuri was more closely related to one of these M. catharinae variants than to the other variant. The present work provides important information regarding genetic variation among Myrmelachista species that may contribute to interpreting the complex morphology of this genus.
Keywords: Formicinae; ISSR molecular markers; Similarity; Twigs; UPGMA